COMPRESSIVE STRENGTH OF TYPE III GYPSUM MIXED WITH WATER OF DIFFERENT WATER HARDNESS LEVEL (Research report) - Dewi Puspitasari; Suci Fikriyati; Debby Saputera (Dentino : Jurnal Kedokteran Gigi, 2019)
Background:  Fabrication of study model to replicate oral dental tissues are needed in dentistry. Type III gypsum is one of gypsum types that is often used to make cast model or die. One of type III gypsum property is compressive strength, which is an ability of the material to resist fracture. Choosing the use of water type should be considered due to final quality of the model and the die. Three different types of water based on water hardness were used in this study.Purpose: to analyze the effect of peat water, tap water and aquades water hardness to compressive strength. Method: This research was pure experimental research design with the post-test only and control design. dental  stone or type III gypsum were mixed with water from peat water, tap water and aquadest (as a control), water hardness were examined. Twenty four die stone were made to  cylinder  with size 40 mm in height and 20 mm in diameter based on ISO 6873:1998 for compressive strength test.  Result: The result of One Way Anova test and Post Hoc Bonferroni test was p= 0.000 (p <0.05)  showing a significant difference among all groups. The mean value of type III  gypsum compressive strength based on water hardness was 12.66 MPa for aquadest (soft); 9.71 MPa for tap water (hard) and 7.40 MPa for peat water (very hard). Conclusion:  there were significant differences of water hardness of peat water, tap water, and aquadest to type III gypsum compressive strength.